Medieval Jewry in Northern France A Political and Social History - Chazan, Robert (Johns Hopkins University Press, 2019)
Originally published in 1974. Focusing on a set of Jewish communities, Robert Chazan tells how, by the eleventh century, French Jews had created for themselves a role as local merchants and moneylenders in adapting to the political, economic, and social limits imposed on them. French society, striving to become more powerful and civilized, was willing to extend aid and protection to the Jews in return for general stimulation of trade and urban life and for the immediate profit realized from taxation. While the authorities were relatively successful in protecting the Jews from others, there was no power to impose itself between the Jews and their protectors. The political and social well-being of the Jews was, therefore, dependent on the will of the governing authorities who taxed their holdings and regulated their activities. During the twelfth and thirteenth centuries, the position of the Jews was constantly under attack by reform elements in the church concerned with Jewish moneylending and blasphemous materials in Jewish books; these reformers were eventually devoted to a serious missionizing effort within the Jewish community. The Jews' situation was further complicated by deep popular animosity, expressing itself in a damaging set of slanders and occasionally in physical violence. Despite the impressive achievements of the Jews in medieval northern France, by the thirteenth century their community was increasingly constricted; and in 1306, they were expelled from royal France by Philip IV. Overcoming the handicap of a lack of copious source material, Chazan analyzes the Jews' political status, their relations with key elements of Christian society, their demographic development, their economic outlets, their internal organization, and their attitudes toward the Christian environment. As it highlights aspects of French society from an unusual perspective, Medieval Jewry in Northern France should be of special interest to the historian of medieval France as well as to the student of Jewish history. This story is also significant for all who are fascinated by the capacity of human groups to respond and adapt creatively to a hostile and limiting environment.